Integration of a 3D-Printed Façade Unit in a Curtain Wall System - Francesco Milano; Ringo Perez Gamote; Nik Eftekhar Olivo; Valeria Piccioni; Po Yen Chen; Caitlin Gallagher; Arno Schlüter; Benjamin Dillenburger; Andreas Luible; Fabio Gramazio; Matthias Kohler (Journal of Facade Design and Engineering)
Plastic materials, known for their lightweight, formability, transparency, and durability, are the state of the art for building façade applications. Recent advances in Large-Scale Robotic 3D Printing (LSR3DP) have enabled the production of bespoke, translucent façade components. While research has largely focused on individual panel properties, there is a gap in developing a comprehensive strategy for integrating these components into a complete façade system. This paper explores the potential of combining custom 3D-printed façade elements with standard curtain wall connections. Quantitative analysis involves constructing and testing a 1 m x 1 m LSR3DP façade assembly for air and water tightness, benchmarking its performance against a conventional curtain wall. Qualitatively, the approach is evaluated through a mock-up, highlighting the architectural possibilities of blending standard and non-standard façade elements. The findings demonstrate that this hybrid system is both technically viable and opens new design possibilities for architects and façade engineers.